The effect of physical exercises to develop the neuromuscular compatibility between the eye and hand in the development of scoring skill in handball for deaf and dumb children (12-15) years - abbas lakhdar,; kayhal ismaail,; بونشادة ياسين, (sports creativity, 2025)
Our study aimed to detect the impact of physical exercises to develop the neuromuscular compatibility between the eye and hand in the development of scoring skill in handball for deaf and dumb children so that we conducted a pilot study at the school of visually impaired children in Djelfa so that our sample consisted of 30 children between the ages of 12 to 15 years. The sample was divided into two control samples of 15 children and the other experimental of 15 children. The eye and hand have a positive and effective effect in the development of accurate scoring skills on goal. It also has an effective and significant impact in developing the skills of throwing and receiving balls and developing the skills of neuromuscular compatibility and scoring in handball.